Plasmacytoma of the Clivus Presenting as Bilateral Sixth Nerve Palsy - Kalwani, Neil; Remenschneider, Aaron K.; Faquin, William; Ferry, Judith; Holbrook, Eric H. (Journal of Neurological Surgery Reports, 2015)
Background and Importance Plasmacytomas are monoclonal proliferations of plasma cells that may arise within soft tissue or bone. The skull base is a rare site for plasmacytomas to occur, and few cases have been reported in the literature. When present in the skull base, plasmacytomas may result in cranial neuropathies and often progress to multiple myeloma more rapidly than other intracranial or skeletal plasmacytomas.Clinical Presentation A 69-year-old man presented with a primary complaint of diplopia and an examination consistent with bilateral abducens nerve palsy. No other deficits were noted. Magnetic resonance imaging of the skull base demonstrated a large T1 isointense moderately enhancing lesion centered within the clivus. Endoscopic biopsy of the mass revealed sheets and aggregates of mature monoclonal plasma cells. The patient's initial systemic work-up revealed that this was a solitary lesion, and he was treated with radiation therapy to the skull base with a durable local effect at 18-month follow-up. Unfortunately he progressed to multiple myeloma with peripheral osteolytic lesions but has been stabilized on chemotherapeutics.Conclusion The clivus is an unusual site for intracranial plasmacytomas, and enhancing lesions must be differentiated from chordoma. Characteristic findings on histopathology include an immunoglobulin light-chain restricted clonal proliferation of plasma cells. Treatment is most commonly radiotherapy with surgery reserved for biopsy and palliation. Clinicians should be aware of the increased risk of progression to multiple myeloma in skull base plasmacytomas.
Keywords: plasmacytoma; clivus; skull base; endoscopic sinus surgery